2018
DOI: 10.1103/physrevb.98.035405
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering complex features in STM images of O adatoms on Ag(110)

Abstract: Recently it was demonstrated that atomic oxygen can cause the extraction of substrate atoms off metal surfaces thus generating chemically different active sites. For Ag(110) this process occurs when O 2 is dosed at 175 K leading, at low coverage, to the formation of single Ag vacancies. Vacancy creation proceeds thereby via the formation of O-AgO complexes, which involve a local reconstruction of the surface and ignite the disruption of the Ag substrate. In this paper, we report on the details of such processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…7,[23][24][25][26] However, a recent study of O/Ag(110) uses a methodology similar to ours. 9 We also note that effects of tip-sample separation have been studied previously by DFT and experimentally for O/Pd(111). 27 Recently, we reported that isolated adsorbed S atoms on a related surface, Cu(100), are imaged as sombreros-protrusions surrounded by a dark ring-at negative sample bias (filled states images), but with increasing bias voltage the central protrusions sink and disappear, converting into an inverted cone-shaped depression at positive sample bias (empty states images).…”
Section: Introductionmentioning
confidence: 63%
“…7,[23][24][25][26] However, a recent study of O/Ag(110) uses a methodology similar to ours. 9 We also note that effects of tip-sample separation have been studied previously by DFT and experimentally for O/Pd(111). 27 Recently, we reported that isolated adsorbed S atoms on a related surface, Cu(100), are imaged as sombreros-protrusions surrounded by a dark ring-at negative sample bias (filled states images), but with increasing bias voltage the central protrusions sink and disappear, converting into an inverted cone-shaped depression at positive sample bias (empty states images).…”
Section: Introductionmentioning
confidence: 63%
“…Surface orientation and image size were calibrated from atomically resolved images of the clean Ag(110) surface (see inset of Figure 1A) or of the (nx1)-O-Ag(110) added row reconstruction. 31,32 Similarly, heights were calibrated on monatomic Ag steps. STS spectra and dI/dV maps were recorded at LHe temperature to minimize thermal drift.…”
Section: Methodsmentioning
confidence: 99%
“…No detailed structures of these clusters have been proposed and the clusters were imaged at 77 K, leading to the clusters appearing streaky or fuzzy in STM images due to the clusters being semi-mobile on the surface. In another related system, it has been demonstrated using low-temperature STM, that oxygen on Ag(110) can produce a variety of features 32,33 . Two of these features contain a linear O-Ag-O structure.…”
Section: Introductionmentioning
confidence: 99%
“…The chain can be regarded as oxygen atoms densely decorating a pre-existing row of Ag atoms. The second feature is an isolated, linear O-Ag-O unit, where the central Ag atom is embedded in (but slightly displaced from) a pre-existing row of Ag atoms 33 . It was proposed that the embedded complex can detach from its lateral surroundings and become “free,” hence aiding in the creation of surface vacancies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation